TRANSFORMING ATTITUDES: A YOUTH INITIATIVE. Issue 2 (1st June 2013) - Trimboli, J; Anderson, L; Rivere, M
Abstract : Background: This collaboration enable nine students in Year 11 and two teachers from Our Lady of Sion College to engage with our patients, their families and staff while exploring a number of topics. Aim: Debunking myths about death, dying and the meaning of Palliative Care. Methods: Patients and family members were interviewed to explore how they have come to understand how the clinical and non-clinical needs of their family members are met. Results: Student Victoria reflects on her experiences 'I could use the clichéd phrase "it changed my life, but in all reality, it did so much more than that. I learnt that hospitals do not have to be places that are starch-white and unfriendly nor do doctors and nurses have to be people to fear. I learnt that courage is an intangible, amazing force that comes from the most unlikely people and places. I learnt that death does not have to be feared; especially not when it could be embraced. I learnt that it is possible for death, the end of someone's life, to be a celebration; a celebration of the life that has occurred rather than the death itself…Finally, I learnt to see past the physical or intellectual disabilities and see the person who is inside. The courageous, friendly, funny, intelligent, remarkable person that they truly are". Discussion: The students, their families and the school community have a new understanding of Palliative Care. Conclusion: This process can be taught to other health care providers—it will create changes in thinking in the community.